O ator que canta um conto: a manipulação de parâmetros musicais na voz do ator - Souza, Mayra Montenegro de (2012)
This research started with an investigation about the theatrical speaking. Through an empirical methodology that analyzed a practical experience of creating a play and bibliographical research, the actress/researcher investigated ways to manipulate musical parameters as tools in the creation process of the actor s voice. The actress/researcher attempted to connect theory and practice, moved by the desire to find a vocal expression in theater that unfolds as living and transforming movement. This dissertation also contains the report of pedagogical experiences, in which the actress/researcher explored strategies to teach the appropriation of musical parameters in the construction of the vocal work of the actor. Considering that speaking in theater is closer to singing than everyday speech, she concluded that the actor may compose music as a music composer does in the elaborating process of building vocal scores. Therefore, she demonstrated that it is of fundamental importance a musical training in the development of the actor.